Enhancing food security sustainability through digital information extension services in rural Uganda: Maize postharvest evidence-based strategies - Jackline Estomihi Mayende Kiwelu; Patrick Ngulube (PLoS ONE, 2025)
Background Postharvest losses caused by poor drying and storage practices lead to maize waste, reduced food availability, unsafe food due to aflatoxin contamination, and income loss for farmers. This exacerbates food insecurity and threatens the livelihoods of rural communities. Leveraging digital solutions to provide quality maize postharvest handling information is critical to mitigating these challenges. Objective This study examined maize postharvest handling extension information services provided by rural agricultural extension officers in selected districts of Uganda, focusing on how evidence-based practices supported by information sources, expert knowledge, and ICT infrastructure ensure the quality and relevance of the information delivered. Methods A convergent parallel mixed-methods design was employed. Data were collected from 312 rural smallholder maize farmers, 22 extension officers, and four information officers. Qualitative data were analyzed thematically using ATLAS.ti version 24, quantitative data were analyzed in SPSS version 29 to generate descriptive statistics and conduct Pearson’s chi-square tests. Findings Agriculture extension officers applied digital evidence-based information practices to improve maize postharvest handling advisory services. The study reported that the most frequently used practices were asking (identifying farmers’ information needs), acquiring (gathering relevant information), appraising (evaluating information quality), and applying (guiding farmers’ decisions). Aggregation (organizing information for accessibility) and assessment (evaluating the effectiveness of applied information) were less practiced. The study suggests a significant relationship between evidence application and maize postharvest handling practices (p = 0.002). No significant relationship between asking farmers’ information needs and maize postharvest handling practices (p = 0.887). The study identified inadequate updated sources of information, insufficient skills in evidence-based practices, and information communication technologies. Conclusion This study suggests that decision-makers update the evidence source and develop continuous professional development (CPD) training programs for rural agricultural extension officers to equip them with knowledge and skills in maize postharvest handling, evidence-based information practices, and new developments in ICTs.